Application of Cooperative Learning Jigsaw Model to Improve Student's Learning Achievement in Chemistry Learning - Sitti Rahmawati; Detris Poba; Magfirah Magfirah; Kusrini Burase (Universitas Tadulako, 2022)
This study aims to improve student achievement in learning chemistry in class X MIA4 at SMA Negeri 1 Palu by applying the Jigsaw Cooperative Learning Model. The Classroom Action Research (CAR) problem can be formulated as follows: Is the Jigsaw Cooperative Learning Model application able to improve student achievement in learning chemistry in class X MIA4 SMAN 1 Palu? CAR is carried out with the following stages to answer the problem: 1. Planning, 2. Implementation. 3. Observation, and 4. Evaluation and Reflection. The study results can be explained as follows several fundamental aspects of learning were successfully improved by applying the Jigsaw Cooperative Learning Model. Such as student activity in collaboration and in completing worksheets independently, actively asking and answering questions, and making students feel happy and enthusiastic. Likewise, the average evaluation of each cycle showed that the % completeness increased. In cycle one, action one was 73.8%, action two 85.5%, and activity three 92.9% increased in cycle two, the average from three actions to 98.0%. It can be concluded that the application of the Jigsaw Cooperative Learning Model can improve student achievement in class X MIA4 SMA Negeri 1.